Comparison Of Different RSM Designs To Predict And Optimize The Acid Violet (AV 7) Adsorption Using RHA-CFA Adsorbent - Mohamad, Ahmad Aqil Asyraaf (Universiti Sains Malaysia, 2021)
Water pollution due to the discharging of industrial wastewater consisting of heavy metals has become a serious issue. A cheap adsorbent is required to support the pollutant adsorption technique. Thus, the main goal of the research is to optimise the preparation and adsorption conditions of activated carbon from cheap raw materials. The production of mangrove-based activated carbon using microwave heating activation is cost-effective because mangrove is abundantly available in Malaysia and microwave heating requires less time and lower electricity. The optimal activated carbon was produced at 616 W and 2 mins under nitrogen flow. The ideal KOH: Char ratio was found to be at IR of 0.75 with 99.67% of activated carbon yield and 77.256% of copper (II) ions removal. The AC was examined by Fourier transform infrared spectroscopy, nitrogen adsorption/desorption isotherm and elemental analysis. Aside from optimisation, the adsorption process using the mangrove adsorbent was examined under various conditions. From the experimental data, the adsorption reached equilibrium after 3 hours at 10ppm and 60℃. Freundlich isotherm models with R2 values of 0.9995 and 1/n smaller than one explains the multilayer and heterogenous nature of adsorption. The maximum adsorption capacity of mangrove-based activated carbon obtained using Langmuir Isotherm was 33.557 mg/g, which shows its intrigue value as a potential adsorbent. Furthermore, the data was well fitted to Pseudo-second-order kinetics models with R2 value of 0.9997. Finally, the thermodynamic analysis revealed that the adsorption studied is endothermic process, and the adsorption is spontaneous at 50 and 60°C.